Transhumane Entwicklungen in Dietmar Daths Roman Venus siegt (2015) - Hans Esselborn (Recherches Germaniques)
This article analyses Dietmar Dath’s novel Venus siegt (2015) by focusing on the topics of transhuman evolution and artificial intelligence. The author, giving his imagination free rein, elaborates on the subject of biotechnology which involves genetic modifications by which human beings, transforming into cyborgs, are connected with mechanical and cybernetic machines. Moreover, the novel introduces the idea of the possible development of an autonomous artificial intelligence. As he imagines the possibility of communication and cooperation between all kinds of intelligences, endowed with consciousness and subjectivity, Dath sketches the outlines of a transhuman society, though not in the strict sense of the term. The novel describes transgressions of the limits of biology and technology according to a conception of intelligence which corresponds to human reason. That is why the world the novel depicts rather consists in an open society, enhanced by machines, inhabited by perfected human beings.